1991
DOI: 10.1097/00001888-199101000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Comparing physiciansʼ specialty interests upon entering medical school with their eventual practice specialties

Abstract: The stability of specialty choices of 519 graduates of the University of Washington School of Medicine were studied by means of a mail survey in 1986. The graduates' actual practice specialties were compared with the one or more specialties each had indicated as possible career specialty choices when they entered medical school. Nearly 70% of the graduates' early choices remained stable, double the percentage found by other studies that based stability on an entering medical student's single choice of a career… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 0 publications
1
27
1
Order By: Relevance
“…16,[18][19][20][21][22][23] Others have demonstrated that career preference at the time of entering medical school may be a significant predictor of students' eventual career choice. 4,[24][25][26] Colwill, for example, suggests that students usually see themselves as either generalists or specialists at the start of medical school. 27 Although there is movement during medical school between the desire to practise family medicine and the desire to practise specialty care, many students end up in careers that are closely related to their choice at the beginning of medical school.…”
mentioning
confidence: 99%
“…16,[18][19][20][21][22][23] Others have demonstrated that career preference at the time of entering medical school may be a significant predictor of students' eventual career choice. 4,[24][25][26] Colwill, for example, suggests that students usually see themselves as either generalists or specialists at the start of medical school. 27 Although there is movement during medical school between the desire to practise family medicine and the desire to practise specialty care, many students end up in careers that are closely related to their choice at the beginning of medical school.…”
mentioning
confidence: 99%
“…Rankings of these characteristics ranged from not very important to essential (2-4) for team worker, good physical health and organized/systematic. Ability to be team leader and sense of humor had the lowest scores, ranging from not at all important to essential (1)(2)(3)(4).…”
Section: Resultsmentioning
confidence: 99%
“…Factors influencing those choices have been studied, as has the time at which career decisions are made. [1][2][3][4][5][6][7][8] Prior to 1993, surgical trainees in Canada did two years of "core" postgraduate training before entry into a surgical subspecialty. Most who chose neurosurgery as a career had rotations on neurosurgical services during the "core" period.…”
mentioning
confidence: 99%
“…Studies examining timing of career choices among medical students have suggested that career interests formed before entry into medical school may be predictive of eventual career choices (10,23,24). In the current study 57.1% of students who had selected surgery had interest in this career even before entry into medical school.…”
Section: Discussionmentioning
confidence: 99%